Lymphatic Microsurgical Preventing Healing Approach (LYMPHA) for primary surgical prevention of breast cancer‐related lymphedema: Over 4 years follow‐up. Issue 6 (26th March 2014) - Boccardo, Francesco; Casabona, Federico; DeCian, Franco; Friedman, Daniele; Murelli, Federica; Puglisi, Maria; C. Campisi, Corrado; Molinari, Lidia; Spinaci, Stefano; Dessalvi, Sara; Campisi, Corradino
<x xml:space="preserve">Abstract</x> Breast cancer‐related lymphedema (LE) represents an important morbidity that jeopardizes breast cancer patients' quality of life. Different attempts to prevent LE brought about improvements in the incidence of the pathology but LE still represents a frequent occurrence in breast cancer survivors. Over 4 years ago, Lymphatic Microsurgical Preventing Healing Approach (LYMPHA) was proposed and long‐term results are reported in this study. From July 2008 to December 2012, 74 patients underwent axillary nodal dissection for breast cancer treatment together with LYMPHA procedure. Volumetry was performed preoperatively in all patients and after 1, 3, 6, 12 months, and once a year. Lymphoscintigraphy was performed in 45 patients preoperatively and in 30 also postoperatively after at least over 1 year. Seventy one patients had no sign of LE, and volumetry was coincident to preoperative condition. In three patients, LE occurred after 8–12 months postoperatively. Lymphoscintigraphy showed the patency of lymphatic‐venous anastomoses at 1–4 years after operation. LYMPHA technique represents a successful surgical procedure for primary prevention of arm LE in breast cancer patients. © 2014 Wiley Periodicals, Inc. Microsurgery 34:421–424, 2014.